Parents' nonstandard work schedules and children's social and emotional wellbeing: A mixed-methods analysis in Germany; Elterliche Schichtarbeit und das soziale und emotionale Wohlbefinden von Kindern: Eine Mixed-Methods Analyse für Deutschland - Jianghong Li; Heike Ohlbrecht; Matthias Pollmann-Schult; Filip Elias Habib (JFR – Journal of Family Research, 2020)
Many children live in households where either one or both parents work nonstandard schedules in the evening, night or weekend. Using a mixed methods design, this study examined whether nonstandard work schedules were linked to lower social and emotional wellbeing in children. The quantitative analysis based on the German Family Panel Study (pairfam) showed that children whose parents worked rotating shifts and other types of nonstandard schedules reported elevated levels of emotional and conduct problems. However, not all types of nonstandard schedules were detrimental to child wellbeing: fixed shift work did not have a negative impact on child social and emotional wellbeing. Overall, the effect of mothers' work schedule on child wellbeing was stronger than that of fathers. The qualitative interviews revealed that nonstandard work schedules made everyday life unsettling and family environment chaotic because it was difficult to plan. Thus, for most families where one or both parents worked such schedules stress was a defining feature of the daily life and parents accepted it as “part of their life”. Families used different strategies to deal with stress and attempted to protect children from it. Contingent on what resources available to them, some families managed well, while others did not cope so well and children were adversely affected. – – Eine beträchtliche Anzahl an Kindern lebt in Familien, in denen ein oder beide Elternteile abends, nachts oder am Wochenende arbeiten. Anhand eines Mixed-Methods Designs untersucht diese Studie, inwiefern solche atypischen Arbeitszeiten das soziale und emotionale Wohlergehen von Kindern negativ beeinflussen. Die quantitativen Analysen auf Basis der deutschen pairfam-Daten zeigen, dass atypische Arbeitszeiten das Wohlbefinden von Kindern beeinträchtigen können. Kinder von Eltern, die in Wechselschicht arbeiten, verzeichnen ein signifikant niedrigeres soziales und emotionales Wohlbefinden als Kinder, deren Eltern keine Schichtarbeit verrichten. Allerdings wird das Wohlbefinden von Kindern nicht beeinträchtigt, wenn die Eltern in fester Schichteinteilung arbeiten. Insgesamt wirkt sich das mütterliche Arbeitszeitarrangement stärker auf das kindliche Wohlbefinden aus als die väterlichen Arbeitszeitregelungen. Die qualitativen Befragungen zeigen, dass atypische Arbeitszeiten zu einem weniger planbaren und turbulenteren familiären Alltagsleben führen. Für die meisten Familien mit atypischen Arbeitszeiten ist Stress ein fester Bestandteil des Alltagslebens. Dabei nutzen Familien – jeweils abhängig von den zur Verfügung stehenden Ressourcen – unterschiedliche Strategien, um Kinder vor den negativen Folgen des elterlichen Stresses zu schützen.
Keywords: 330; nonstandard work schedules; shift work; parents; social and emotional wellbeing; children; mixed methods; pairfam; atypische Arbeitszeiten; Schichtarbeit; Kinder; soziales und emotionales Wohlbefinden